PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN MODEL PROBLEM BASED LEARNING MATERI BANGUNRUANG SISI LENGKUNG DI SMP - Supadmi, Supadmi; Rif at, Mohamad; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractLearning is a process of interaction between students, students with educators, and learning resources. Besides, learning is also the process of developing potential and character building of each students as a result of the synergy between educators that take place in school, family and society. The development model which used was prototype model, according to Plom and Nieveen with several modifications. This research was conducted in class IX A of SMP N 01 Kubu with the number of students is 38 students, that chosen based on purposive sampling. This instruments which used in this research includeaspects of validity, practicality, and effectiveness.in the case, the development product are said to be valid if they complete the criteria of the experts. The development product are said to be practical if they meet the practicality criteria and can be applied in the field. The development products are said to be affective if they carried out in full learning and accomplishment of competence by students individually. Several stages which used in this research are brainstorming, gathering information and data, sharing information and discussion to find solution in solving any problems, and reflection stage RPP problem based learning and its supporting devices are declared valid, practical and also effective to be applied. Keywords: learning plan, problem based learning, curved side geometry, SMP N 1 Kubu